Soft magnetic powder, pressed powder core, magnetic element, electronic equipment and moving objects
By using amorphous metal particles with specific composition and heat treatment technology, the problem of large core loss in the high frequency regions of the prior art is solved, and soft magnetic powder with low coercivity and high magnetic permeability is achieved, suitable for powder pressing bodies miniaturization and efficiency.
Patent Information
- Application Number
- CN202210498457.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2021-05-12
- Filing Date
- 2022-05-09
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2042-05-09
AI Technical Summary
The existing iron-based metal glass alloy powder has a large core loss in the high-frequency region, and its composition has not been fully considered, making it difficult to achieve low coercivity soft magnetic powder.
The amorphous metal particles represented by the composition formula Fe100-a-b-c-d-e-f-gCraSibBcCdAleTifCog are used to reduce coercive forces and improve magnetic permeability through specific atomic percentage ranges and heat treatment techniques.
It realizes suppressing hysteresis and eddy current losses in high-frequency areas, taking into account high magnetic permeability and low coercivity, and is suitable for miniaturized and efficient pressing powders.
Smart Images

Figure CN115346747B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to soft magnetic powder, a powder compact magnetic core, a magnetic component, an electronic device, and a moving body. Background Art
[0002] Patent Document 1 discloses an iron-based metallic glass alloy powder represented by a compositional formula (Fe 1-s-t Co s Ni t ) 100-x-y {(Si a B b ) m (P c C d ) n} x M y , where x, y, s, and t in the compositional formula satisfy 19 ≤ x ≤ 30, 0 < y ≤ 6, 0 ≤ s ≤ 0.35, 0 ≤ t ≤ 0.35, and s + t ≤ 0.35. Further, in this iron-based metallic glass alloy powder, at least one of Cr or Zr is added as a corrosion resistance modifying component, and at least one of V, Ti, Ta, Cu, and Mn is added as a corrosion resistance modifying sub-component.
[0003] Such an iron-based metallic glass alloy powder can achieve an improvement in magnetic properties because it contains an amorphous single phase. Further, in this iron-based metallic glass alloy powder, the corrosion resistance and the resistivity are improved because the corrosion resistance modifying component and the corrosion resistance modifying sub-component are added.
[0004] Patent Document 1: Japanese Unexamined Patent Application Publication No. 2014-169482
[0005] Powder compacts such as powder compact magnetic cores made of soft magnetic powder are also often used in the high-frequency region. In the high-frequency region, since there is a tendency to increase the core loss of the powder compact, suppressing the core loss has become a problem. The composition of the soft magnetic powder easily contributes to suppressing the hysteresis loss in the core loss. In order to suppress the hysteresis loss, it is necessary to reduce the coercive force of the soft magnetic powder.
[0006] However, in the iron-based metallic glass alloy powder described in Patent Document 1, the influence of its composition on the coercive force is not considered. Therefore, how to achieve soft magnetic powder having good magnetic properties and low coercive force by an amorphous alloy has become a problem. Summary of the Invention
[0007] The soft magnetic powder according to an application example of the present invention is characterized in that
[0008] it contains: amorphous metal particles having a compositional formula Fe 100-a-b-c-d-e-f-g Cra Si b B c C d Al e Ti f Co g Represents the composition.
[0009] [Wherein, a, b, c, d, e, f and g are numbers representing atomic % and satisfy:
[0010] 0 <a≤3.0,
[0011] 5.0≤b≤15.0,
[0012] 7.0≤c≤15.0,
[0013] 0.1≤d≤3.0,
[0014] 0 <e≤0.016,
[0015] 0 <f≤0.009,
[0016] 0≤g≤0.025.]
[0017] A powder magnetic core according to an application example of the present invention is characterized in that:
[0018] The soft magnetic powder according to the application example of the present invention is contained.
[0019] A magnetic element according to an application example of the present invention is characterized in that:
[0020] A powder magnetic core according to an application example of the present invention is provided.
[0021] An electronic device according to an application example of the present invention is characterized in that:
[0022] A magnetic element according to an application example of the present invention is provided.
[0023] A moving object according to an application example of the present invention is characterized in that:
[0024] A magnetic element according to an application example of the present invention is provided. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 It is a top view schematically showing a toroidal coil component.
[0026] Figure 2 It is a perspective view schematically showing a closed magnetic circuit type coil component.
[0027] Figure 3 It is a perspective view showing a mobile personal computer as an electronic device including the magnetic element according to the embodiment.
[0028] Figure 4 It is a top view showing a smartphone as an electronic device including the magnetic element according to the embodiment.
[0029] Figure 5 It is a perspective view showing a digital still camera as an electronic device including a magnetic element according to the embodiment.
[0030] Figure 6 It is a perspective view showing a car as a moving object including the magnetic element according to the embodiment.
[0031] Description of Reference Numerals
[0032] 10: coil component; 11: pressed powder core; 12: wire; 20: coil component; 21: pressed powder core; 22: wire; 100: display unit; 1000: magnetic element; 1100: personal computer; 1102: keyboard; 1104: main body; 1106: display unit; 1200: smart phone; 1202: operation button; 1204: answering port; 1206: talking port; 1300: digital still camera; 1302: housing; 1304: light receiving unit; 1306: shutter button; 1308: memory; 1500: automobile. DETAILED DESCRIPTION
[0033] Hereinafter, the soft magnetic powder, the powder magnetic core, the magnetic element, the electronic device, and the moving body of the present invention will be described in detail based on the preferred embodiments shown in the drawings.
[0034] 1. Soft magnetic powder
[0035] The soft magnetic powder according to the embodiment is a metal powder exhibiting soft magnetism and can be used for any purpose, for example, by bonding particles to each other with a binder to produce various powder bodies such as powder cores and electromagnetic wave absorbing materials.
[0036] 1.1. Composition
[0037] The soft magnetic powder according to the embodiment contains amorphous metal particles having a composition formula of Fe 100-a-b-c-d-e-f-g Cr a Si b B c C d Al e Ti f Co g Represents the composition.
[0038] a, b, c, d, e, f and g are numbers indicating atomic %. a, b, c, d, e, f and g satisfy:
[0039] 0 <a≤3.0,
[0040] 5.0≤b≤15.0,
[0041] 7.0≤c≤15.0,
[0042] 0.1≤d≤3.0,
[0043] 0 <e≤0.016,
[0044] 0 <f≤0.009,
[0045] 0≤g≤0.025.
[0046] Since such a soft magnetic powder contains amorphous metal particles, the magnetic anisotropy is reduced compared to the case where crystalline metal particles are contained, and magnetic properties such as magnetic permeability can be improved, and coercive force can be reduced.
[0047] In addition, since the amorphous metal particles have the above-mentioned composition, the soft magnetic powder can be further reduced in coercivity when subjected to heat treatment. Heat treatment plays a role in reducing various defects or anisotropy (stress-induced anisotropy) introduced when manufacturing the soft magnetic powder. Therefore, the soft magnetic powder is designed in anticipation of the reduction in coercivity caused by heat treatment, but the reduction is limited depending on the composition.
[0048] In contrast, by containing amorphous metal particles having the above-mentioned composition, in the soft magnetic powder involved in this embodiment, the crystallization of the amorphous metal caused by heat treatment can be suppressed, and the coercive force can be sufficiently reduced by heat treatment. Therefore, in the soft magnetic powder after heat treatment, high magnetic permeability and low coercive force can be taken into account. By using such soft magnetic powder, a powder compact that helps to miniaturize and improve the efficiency of magnetic elements can be achieved. It should be noted that in this specification, various defects and anisotropy are also referred to as "deformation".
[0049] The soft magnetic powder may contain any soft magnetic powder or non-magnetic powder in addition to the amorphous metal particles having the above composition. The content of the amorphous metal particles is preferably 50% by mass or more, more preferably 80% by mass or more, and further preferably 90% by mass or more.
[0050] Hereinafter, the composition of the amorphous metal particles will be described.
[0051] Fe (iron) has a great influence on the basic magnetic properties and mechanical properties of the amorphous metal particles according to the embodiment.
[0052] The content rate of Fe is represented by 100 - a - b - c - d - e - f - g. Here, due to the influence of impurities, a deviation of ±0.50 atomic% or less centered on 100 - a - b - c - d - e - f - g is allowed to exist.
[0053] The content rate of Fe is not particularly limited, preferably 70.0 atomic% or more and 81.0 atomic% or less, more preferably 72.0 atomic% or more and 75.0 atomic% or less.
[0054] It should be noted that when the content rate of Fe is lower than the lower limit value, the magnetic permeability or saturation magnetic flux density of the amorphous metal particles may decrease. On the other hand, when the content rate of Fe exceeds the upper limit value, it may be difficult to stably form an amorphous structure when manufacturing the amorphous metal particles.
[0055] Cr (chromium) plays a role in improving the corrosion resistance of the amorphous metal particles. It is considered that this is because a passive film mainly composed of Cr oxide is formed. By improving the corrosion resistance, the oxidation of the amorphous metal particles can be inhibited, and the reduction of magnetic properties due to oxidation can be inhibited. In addition, the passive film also helps to improve the inter - particle insulation of the amorphous metal particles and inhibit the eddy current loss of the compacted powder.
[0056] The content rate a of Cr satisfies 0 < a ≤ 3.0, preferably satisfies 1.1 ≤ a ≤ 2.7, more preferably satisfies 1.2 ≤ a ≤ 2.5. When the content rate a of Cr is lower than the lower limit value, the corrosion resistance decreases, and the magnetic properties of the amorphous metal particles may deteriorate over time. On the other hand, when the content rate a of Cr exceeds the upper limit value, the amorphization is hindered when manufacturing the amorphous metal particles, so the magnetic anisotropy becomes large and the magnetic permeability may decrease.
[0057] Si (silicon) promotes amorphization when manufacturing the amorphous metal particles. Thus, when heat - treating the soft magnetic powder, the crystallization of the amorphous metal particles is inhibited. In addition, Si also helps to improve the magnetic permeability of the amorphous metal particles.
[0058] The content rate b of Si satisfies 5.0 ≤ b ≤ 15.0, preferably satisfies 8.0 ≤ b ≤ 13.5, more preferably satisfies 10.5 ≤ b ≤ 12.0. When the content rate b of Si is lower than the lower limit value, the amorphization is hindered, and the magnetic permeability of the amorphous metal particles may decrease. On the other hand, when the content rate b of Si exceeds the upper limit value, the saturation magnetic flux density may decrease.
[0059] B (boron) promotes amorphization when manufacturing amorphous metal particles. Thus, when heat-treating the soft magnetic powder, crystallization of the amorphous metal particles is suppressed. In addition, B also helps to increase the magnetic permeability of the amorphous metal particles. Furthermore, by using Si and B in combination, due to the difference in atomic radii between the two, amorphization can be synergistically promoted.
[0060] The content rate c of B satisfies 7.0 ≤ c ≤ 15.0, preferably satisfies 8.0 ≤ c ≤ 13.5, and more preferably satisfies 10.5 ≤ c ≤ 12.0. When the content rate c of B is lower than the lower limit value, amorphization is hindered, and the magnetic permeability of the amorphous metal particles may decrease. On the other hand, when the content rate c of B exceeds the upper limit value, the saturation magnetic flux density may decrease.
[0061] C (carbon) reduces the viscosity of the melt when melting the raw materials of the amorphous metal particles, making amorphization and micronization easier. Thus, amorphous metal particles with a small diameter and high magnetic permeability can be achieved. As a result, in the high-frequency region, not only can magnetic hysteresis loss be suppressed, but also eddy current loss can be suppressed.
[0062] The content rate d of C satisfies 0.1 ≤ d ≤ 3.0, preferably satisfies 1.3 ≤ d ≤ 2.8, and more preferably satisfies 1.7 ≤ d ≤ 2.5. When the content rate d of C is lower than the lower limit value, the viscosity of the melt does not decrease sufficiently, and the shape of the amorphous metal particles is likely to be different. Therefore, the packing property during powder pressing decreases, and it may not be possible to sufficiently increase the saturation magnetic flux density of the compact. On the other hand, when the content rate d of C exceeds the upper limit value, amorphization is hindered, and the magnetic permeability of the amorphous metal particles may decrease.
[0063] By adding a small amount of Al (aluminum), when heat-treating the amorphous metal particles, the reduction of deformation is promoted. Therefore, in the heat-treated soft magnetic powder, high magnetic permeability and low coercivity can be achieved at the same time.
[0064] The content rate e of Al satisfies 0 < e ≤ 0.016, preferably satisfies 0.001 ≤ e ≤ 0.009, and more preferably satisfies 0.003 ≤ e ≤ 0.007. When the content rate e of Al is lower than the lower limit value, it may not be possible to sufficiently reduce the coercivity when heat-treating the amorphous metal particles. On the other hand, when the content rate e of Al exceeds the upper limit value, amorphization is hindered, and when heat-treating the amorphous metal particles, crystallization may easily occur.
[0065] By adding a small amount of Ti (titanium), when heat-treating the amorphous metal particles, the reduction of deformation is promoted. Therefore, in the heat-treated soft magnetic powder, high magnetic permeability and low coercivity can be achieved at the same time.
[0066] The content fraction f of Ti satisfies 0 < f ≤ 0.009, preferably 0.001 ≤ f ≤ 0.008, and more preferably 0.003 ≤ f ≤ 0.007. When the content fraction f of Ti is lower than the lower limit value, it may not be possible to sufficiently reduce the coercivity when performing heat treatment on the amorphous metal particles. On the other hand, when the content fraction f of Ti exceeds the upper limit value, the formation of amorphous is hindered, and crystallization may easily occur when performing heat treatment on the amorphous metal particles.
[0067] By adding a small amount of Co (cobalt) together with Al or Ti, when performing heat treatment on the amorphous metal particles, it acts synergistically with Al or Ti to promote the reduction of deformation. Therefore, in the soft magnetic powder after heat treatment, high magnetic permeability and low coercivity can be achieved simultaneously.
[0068] The content fraction g of Co satisfies 0 ≤ g ≤ 0.025, preferably 0.001 ≤ g ≤ 0.020, and more preferably 0.003 ≤ g ≤ 0.015. When the content fraction g of Co is lower than the lower limit value, it may not be possible to sufficiently reduce the coercivity when performing heat treatment on the amorphous metal particles. On the other hand, when the content fraction g of Co exceeds the upper limit value, the formation of amorphous is hindered, and crystallization may easily occur when performing heat treatment on the amorphous metal particles.
[0069] In addition, by optimizing the quantitative ratio with Al and Ti, the reduction of deformation during heat treatment can be particularly promoted.
[0070] Specifically, e and f in the composition formula preferably satisfy 0.20 ≤ e / f ≤ 2.50, more preferably 0.40 ≤ e / f ≤ 2.00, and further preferably 0.60 ≤ e / f ≤ 1.50. When e / f is within the above range, since the balance of the amounts of Al and Ti is optimized, high magnetic permeability and low coercivity of the amorphous metal particles can be particularly achieved through heat treatment.
[0071] Furthermore, by optimizing the quantitative ratio with Al and Co, the reduction of deformation during heat treatment can be particularly promoted.
[0072] Specifically, e and g in the composition formula preferably satisfy 0.10 ≤ e / g ≤ 3.00, more preferably 0.20 ≤ e / g ≤ 2.00, and further preferably 0.30 ≤ e / f ≤ 1.00. When e / g is within the above range, since the balance of the amounts of Al and Co is optimized, high magnetic permeability and low coercivity of the amorphous metal particles can be particularly achieved through heat treatment.
[0073] In addition, the amorphous metal particles according to the embodiment are composed of the above composition formula Fe 100-a-b-c-d-e-f- g Cr a Sib B c C d Al e Ti f Co g In addition to the composition shown, impurities may be contained. As impurities, all elements other than the above elements may be listed, but the total content of the impurities is preferably 0.50 atomic % or less. If within this range, the impurities are unlikely to hinder the effect of the present invention.
[0074] The content of each element as impurity is preferably 0.05 atomic % or less. Within this range, the impurities are unlikely to inhibit the effects of the present invention, and thus inclusion is permitted.
[0075] The composition of the amorphous metal particles according to the embodiment has been described above, and the composition and impurities are determined by the following analysis method.
[0076] As the analysis method, for example, there can be listed the iron and steel-atomic absorption spectrometry specified in JIS G 1257:2000, the iron and steel-ICP emission spectrometry specified in JIS G 1258:2007, the iron and steel-spark discharge emission spectrometry specified in JIS G 1253:2002, the iron and steel-fluorescent X-ray analysis specified in JIS G1256:1997, the gravimetric titration-absorptiometry specified in JIS G 1211 to G 1237, and the like.
[0077] Specifically, for example, there can be cited solid-state emission spectrometers manufactured by SPECTRO, in particular, spark discharge emission spectrometer, model: SPECTROLAB, type: LAVMB08A; and ICP device CIROS120 manufactured by Rigaku Corporation.
[0078] In particular, when determining C (carbon) and S (sulfur), the oxygen stream combustion (high frequency induction heating furnace combustion)-infrared absorption method specified in JIS G 1211: 2011 may be used. Specifically, a carbon and sulfur analyzer, CS-200, manufactured by LECO Corporation may be used.
[0079] In particular, when determining N (nitrogen) and O (oxygen), the nitrogen quantitative method for iron and steel specified in JIS G 1228: 1997 and the oxygen quantitative method general rules for metal materials specified in JIS Z 2613: 2006 can also be used. Specifically, the oxygen and nitrogen analyzer TC-300 / EF-300 manufactured by LECO can be cited.
[0080] If necessary, an insulating film may be provided on the surface of the particles of the soft magnetic powder. Examples of the insulating film include glass materials, ceramic materials, and resin materials.
[0081] 1.2.Powder characteristics
[0082] The average particle size D50 of the soft magnetic powder involved in the embodiment is not particularly limited, and is preferably 1 μm or more and 50 μm or less, more preferably 3 μm or more and 30 μm or less, and further preferably 5 μm or more and 20 μm or less. By using a soft magnetic powder with such an average particle size, the path through which the eddy current flows can be shortened. As a result, a soft magnetic powder that can fully suppress the eddy current loss generated in the particles can be obtained.
[0083] When the average particle size of the soft magnetic powder is lower than the lower limit, the soft magnetic powder becomes too fine, so the filling property of the soft magnetic powder may be reduced. As a result, the molding density of the powder core as an example of the powder compact is reduced, so the magnetic permeability and magnetic flux density of the powder core may be reduced. On the other hand, when the average particle size of the soft magnetic powder exceeds the upper limit, the eddy current loss generated in the particles cannot be fully suppressed, and the core loss of the powder core may increase.
[0084] The average particle diameter D50 of the soft magnetic powder is determined as a particle diameter at which the cumulative value from the smaller diameter side reaches 50% in a volume-based particle size distribution obtained by a laser diffraction method.
[0085] Regarding the soft magnetic powder involved in the embodiment, in the volume-based particle size distribution obtained by laser diffraction method, the particle size when the accumulation is 10% from the small diameter side is set to D10, and the particle size when the accumulation is 90% from the small diameter side is set to D90. At this time, (D90-D10) / D50 is preferably greater than 1.0 and less than 1.5, and more preferably greater than 1.0 and less than 1.3. (D90-D10) / D50 is an index indicating the degree of expansion of the particle size distribution. By making this index within the above range, the filling property of the soft magnetic powder becomes good. Therefore, a powder compact having particularly high magnetic properties such as magnetic permeability and magnetic flux density can be obtained.
[0086] 1.3.Physical properties
[0087] The coercivity of the soft magnetic powder involved in the embodiment is not particularly limited, but is preferably 3.0 [Oe] or less (239 [A / m] or less), and more preferably 0.1 [Oe] or more and 2.0 [Oe] or less (8.0 [A / m] or more and 159 [A / m] or less). By using a soft magnetic powder with a small coercivity, a powder compact can be manufactured that can fully suppress hysteresis loss even when used in a high-frequency region.
[0088] The coercive force of the soft magnetic powder can be measured by, for example, a vibrating sample magnetometer such as TM-VSM1230-MHHL manufactured by Tamagawa Seisakusho Co., Ltd.
[0089] The magnetic permeability of the soft magnetic powder according to the embodiment when made into a powder compact is preferably 15 or more, more preferably 17 or more at a measurement frequency of 100 kHz. Such a soft magnetic powder contributes to the realization of a powder core having excellent magnetic properties.
[0090] The so-called magnetic permeability of the powder compact is, for example, the relative magnetic permeability obtained by forming the powder compact into a toroidal shape from the self-inductance of the closed magnetic circuit magnetic core coil, i.e., the effective magnetic permeability. The magnetic permeability is measured using an impedance analyzer at a measurement frequency of 100 kHz. In addition, the number of turns of the winding is 7, and the wire diameter of the winding is 0.6 mm.
[0091] 2. Preparation method of soft magnetic powder
[0092] Next, an example of a method for producing the above-mentioned soft magnetic powder will be described.
[0093] The above-mentioned amorphous metal particles can be powders manufactured by any method. As examples of manufacturing methods, for example, in addition to various atomization methods such as water atomization, gas atomization, and rotating water flow atomization, pulverization methods, etc. can also be listed. Among them, the amorphous metal particles are preferably particles manufactured by atomization. By atomization, powders with small and good particle shapes can be efficiently manufactured. Therefore, soft magnetic powders with particularly high filling properties can be obtained.
[0094] The atomization method is a method of producing metal powder by causing molten metal to collide with a high-speed jet of liquid or gas to pulverize the molten metal and then cool it.
[0095] Among them, the water atomization method is a method of producing metal powder from molten metal by using a liquid such as water as a coolant, spraying it in an inverted cone shape concentrated at one point, and causing molten metal to flow down and collide with the concentrated point.
[0096] In addition, the rotating water flow atomization method is a method of producing metal powder by supplying coolant along the inner circumference of a cooling cylinder, causing it to rotate along the inner circumference, and blowing a jet of liquid or gas toward the molten metal to collect the scattered molten metal into the coolant.
[0097] In the atomization method, the cooling rate when cooling the molten metal is preferably 1×10 4 ℃ / s or more, more preferably 1×10 5℃ / s or more. Through such rapid cooling, the solidification is achieved while the atomic arrangement in the molten metal state is preserved, so that amorphous metal particles with a particularly high degree of amorphization can be obtained, and the deviation of the composition ratio between the amorphous metal particles can be suppressed. As a result, a homogeneous soft magnetic powder can be obtained.
[0098] By subjecting the amorphous metal particles produced by the above-described method to heat treatment, the magnetic properties can be improved and the coercive force can be further reduced.
[0099] When the crystallization temperature of the amorphous metal particles is defined as Tx, the heating temperature in the heat treatment is preferably Tx-100°C or higher and lower than Tx, and more preferably Tx-50°C or higher and lower than Tx.
[0100] When the heating temperature is within the above range, the heating time in the heat treatment is preferably 5 minutes to 120 minutes, more preferably 5 minutes to 60 minutes.
[0101] By performing heat treatment under such heating conditions, residual stress caused by rapid solidification generated when producing amorphous metal particles can be alleviated. As a result, deformation in the amorphous metal particles is alleviated, coercivity can be reduced, and magnetic properties can be improved.
[0102] The produced soft magnetic powder may be classified as required. Examples of the classification method include dry classification such as sieving classification, inertial classification, and centrifugal classification, and wet classification such as sedimentation classification.
[0103] 3.Powder cores and magnetic components
[0104] Next, a dust core and a magnetic element according to an embodiment will be described.
[0105] The magnetic element according to the embodiment can be applied to various magnetic elements having a magnetic core, such as a choke coil, an inductor, a noise filter, a reactor, a transformer, a motor, an actuator, a solenoid valve, a generator, etc. In addition, the powder magnetic core according to the embodiment can be applied to the magnetic core of these magnetic elements.
[0106] Hereinafter, two types of coil components will be described as representative examples of magnetic elements.
[0107] 3.1. Ring type
[0108] First, a toroidal coil component as an example of the magnetic element according to the embodiment will be described.
[0109] Figure 1 It is a top view schematically showing a toroidal coil component.
[0110] Figure 1 The coil component 10 shown has a ring-shaped powder magnetic core 11 and a conductive wire 12 wound around the powder magnetic core 11. Such a coil component 10 is generally called a toroidal coil.
[0111] The powdered magnetic core 11 is obtained by mixing the soft magnetic powder and a binding material involved in the embodiment, supplying the obtained mixture to a molding die, and performing pressurization and molding. That is, the powdered magnetic core 11 is a powder body containing the soft magnetic powder involved in the embodiment. In such a powdered magnetic core 11, the coercive force of the soft magnetic powder is low and the magnetic permeability is high. Therefore, the coil component 10 having the powdered magnetic core 11 has low core loss in the high-frequency region and high magnetic properties such as magnetic permeability and magnetic flux density. Therefore, when the coil component 10 is mounted on an electronic device, etc., the power consumption of the electronic device, etc. can be reduced, and high performance and miniaturization can be achieved.
[0112] As the constituent materials of the binding material used in the manufacture of the powder magnetic core 11, for example, organic materials such as silicone resins, epoxy resins, phenol resins, polyamide resins, polyimide resins, and polyphenylene sulfide resins, and inorganic materials such as phosphates such as magnesium phosphate, calcium phosphate, zinc phosphate, manganese phosphate, and cadmium phosphate, and silicates such as sodium silicate, etc., are listed, and thermosetting polyimide or epoxy resin is particularly preferred. These resin materials are easily cured by heating and have excellent heat resistance. Therefore, the ease of manufacture and heat resistance of the powder magnetic core 11 can be improved. It should be noted that the binding material can be added as needed or omitted.
[0113] In addition, the ratio of the binding material to the soft magnetic powder is slightly different, preferably from 0.5 mass % to 5.0 mass %, and more preferably from 1.0 mass % to 3.0 mass %, depending on the target magnetic properties or mechanical properties, the permissible eddy current loss, etc. of the manufactured powder magnetic core 11. Thus, the particles of the soft magnetic powder can be fully bonded to each other, and the coil component 10 with excellent magnetic properties can be obtained.
[0114] Various additives may be added to the mixture for any purpose as needed.
[0115] The conductive wire 12 may be made of a material having high conductivity, such as a metal material containing Cu, Al, Ag, Au, Ni, etc. An insulating film may be provided on the surface of the conductive wire 12 as necessary.
[0116] It should be noted that the shape of the powder core 11 is not limited to Figure 1The ring shape shown may be, for example, a shape in which a part of the ring is missing, a shape in which the longitudinal direction is linear, a sheet shape, a film shape, or the like.
[0117] Furthermore, the powder core 11 may contain a soft magnetic powder or a non-magnetic powder other than the soft magnetic powder according to the above-mentioned embodiment, as necessary.
[0118] As described above, the coil component 10 as a magnetic element includes the powder core 11 containing the soft magnetic powder described above. This makes it possible to realize the coil component 10 having low core loss and excellent magnetic characteristics.
[0119] 3.2. Closed magnetic circuit type
[0120] Next, a closed magnetic circuit type coil component will be described as an example of the magnetic element according to the embodiment.
[0121] Figure 2 It is a perspective view schematically showing a closed magnetic circuit type coil component.
[0122] The closed magnetic circuit type coil component will be described below. However, in the following description, the differences from the annular type coil component will be mainly described, and the description of the same matters will be omitted.
[0123] like Figure 2 As shown, the coil component 20 involved in this embodiment is formed by burying the conductive wire 22 formed into a coil shape inside the powder core 21. That is, the coil component 20 as a magnetic element has a powder core 21 containing the above-mentioned soft magnetic powder, and the conductive wire 22 is molded by the powder core 21. The powder core 21 has the same structure as the above-mentioned powder core 11. As a result, the coil component 20 with low core loss and excellent magnetic properties can be realized.
[0124] The coil component 20 of such a form is easy to obtain a relatively small component. In addition, the coil component 20 has high magnetic properties and low core loss. Therefore, when the coil component 20 is mounted on an electronic device, the power consumption of the electronic device can be reduced, and high performance and miniaturization can be achieved.
[0125] Furthermore, since the lead wire 22 is buried inside the powder core 21, a gap is unlikely to be generated between the lead wire 22 and the powder core 21. Therefore, vibration caused by magnetostriction of the powder core 21 can be suppressed, and noise caused by the vibration can be suppressed.
[0126] It should be noted that the shape of the powder core 21 is not limited to Figure 2 The shape shown may also be a sheet, a film, etc.
[0127] Furthermore, the powder core 21 may contain a soft magnetic powder or a non-magnetic powder other than the soft magnetic powder according to the above-mentioned embodiment, as necessary.
[0128] 4. Electronic devices
[0129] Next, based on Figure 3 to Figure 5 An electronic device including the magnetic element according to the embodiment will be described.
[0130] Figure 3 It is a perspective view showing a mobile personal computer as an electronic device including the magnetic element according to the embodiment. Figure 3 The personal computer 1100 shown in the figure includes a main body 1104 including a keyboard 1102 and a display unit 1106 including a display unit 100. The display unit 1106 is rotatably supported by the main body 1104 via a hinge structure. Such a personal computer 1100 has a built-in magnetic element 1000 such as a choke coil or inductor for a switching power supply, a motor, or the like.
[0131] Figure 4 It is a top view showing a smartphone as an electronic device including the magnetic element according to the embodiment. Figure 4 The smartphone 1200 shown includes a plurality of operation buttons 1202, an earpiece 1204, and a talk port 1206. The display unit 100 is disposed between the operation buttons 1202 and the earpiece 1204. Such a smartphone 1200 has magnetic components 1000 such as an inductor, a noise filter, and a motor built therein.
[0132] Figure 5 13 is a perspective view showing a digital still camera as an electronic device including a magnetic element according to an embodiment. The digital still camera 1300 generates an imaging signal by photoelectrically converting an optical image of a subject using an imaging element such as a CCD (Charge Coupled Device).
[0133] Figure 5 The digital still camera 1300 shown in the figure has a display unit 100 provided on the back of a housing 1302. The display unit 100 functions as a viewfinder for displaying an electronic image of a subject. In addition, a light receiving unit 1304 including an optical lens or a CCD is provided on the front side of the housing 1302, that is, the back side in the figure.
[0134] When the photographer checks the subject image displayed on the display unit 100 and presses the shutter button 1306, the imaging signal of the CCD at that time is transferred and stored in the memory 1308. Such a digital still camera 1300 also has a magnetic element 1000 such as an inductor or a noise filter built in.
[0135] As an electronic device according to an embodiment of the present invention, in addition to Figure 3 Personal computers, Figure 4 Smartphones, Figure 5 In addition to still digital cameras, examples include mobile phones, tablet terminals, watches, inkjet printers and other inkjet ejection devices, notebook personal computers, televisions, cameras, video recorders, car navigation devices, pagers, electronic notepads, electronic dictionaries, calculators, electronic game consoles, word processors, workstations, videophones, anti-theft television monitors, electronic binoculars, POS terminals, electronic thermometers, blood pressure monitors, blood glucose meters, electrocardiogram measuring devices, ultrasonic diagnostic devices, electronic endoscopes and other medical equipment, fish finders, various measuring equipment, measuring instruments for vehicles, aircraft, and ships, mobile body control equipment such as automobile control equipment, aircraft control equipment, railway vehicle control equipment, and ship control equipment, flight simulators, etc.
[0136] As described above, such an electronic device includes the magnetic element according to the embodiment. Thus, the effects of the magnetic element such as low coercive force and high magnetic permeability can be enjoyed, and the performance of the electronic device can be improved.
[0137] 5. Mobile body
[0138] Next, based on Figure 6 A moving body including the magnetic element according to the present embodiment will be described.
[0139] Figure 6 It is a perspective view showing a car as a moving object including the magnetic element according to the embodiment.
[0140] The magnetic element 1000 is built into the automobile 1500. Specifically, the magnetic element 1000 is built into various automobile parts such as a car navigation system, an anti-lock braking system (ABS), an engine control unit, a battery control unit of a hybrid car or an electric car, a body posture control system, an electronic control unit (ECU: electronic control unit) such as an automatic driving system, a drive motor, a generator, and an air conditioning unit.
[0141] As described above, such a moving body includes the magnetic element according to the embodiment. Thus, the effects of the magnetic element such as low coercive force and high magnetic permeability can be enjoyed, and the high performance of the moving body can be achieved.
[0142] It should be noted that the mobile body involved in this embodiment has Figure 6 In addition to the automobile shown, for example, it may be a motorcycle, a bicycle, an aircraft, a helicopter, an unmanned aerial vehicle, a ship, a submarine, a train, a rocket, a spacecraft, etc.
[0143] As mentioned above, the soft magnetic powder, the powder magnetic core, the magnetic element, the electronic device, and the moving body of the present invention have been described based on the preferred embodiments, but the present invention is not limited thereto.
[0144] For example, in the above-described embodiment, as an example of application of the soft magnetic powder of the present invention, a compressed powder body such as a powder core is cited and described. However, the application example is not limited to this, and for example, magnetic devices such as a magnetic fluid, a magnetic head, and a magnetic shielding sheet may also be used.
[0145] Furthermore, the shapes of the powder magnetic core and the magnetic element are not limited to those shown in the drawings, and may be any shapes.
[0146] Example
[0147] Next, specific examples of the present invention will be described.
[0148] 6. Manufacture of soft magnetic powder
[0149] 6.1. Sample No.1
[0150] First, the raw materials are melted in a high-frequency induction furnace and powdered by water atomization to obtain amorphous metal particles, which are then classified using a sieve.
[0151] Next, the classified amorphous metal particles were heat treated at 300° C. for 30 minutes in a nitrogen atmosphere to obtain a soft magnetic powder of Sample No. 1.
[0152] The composition of the obtained amorphous metal particles is shown in Table 1. It should be noted that, in order to determine the composition, a solid emission spectrometer (spark emission analyzer) manufactured by SPECTRO was used, model: SPECTROLAB, type: LAVMB08A. In addition, a carbon·sulfur analyzer CS-200 manufactured by LECO was used for the quantitative analysis of C (carbon).
[0153] 6.2 Sample No. 2 to 21
[0154] Except that the composition of the amorphous metal particles was as shown in Table 1 or Table 2, a soft magnetic powder was obtained in the same manner as in Sample No. 1.
[0155] In addition, in Table 1 and Table 2, among the soft magnetic powders of each sample No., those corresponding to the present invention are described as “Examples”, and those not corresponding to the present invention are described as “Comparative Examples”.
[0156] 7. Evaluation of soft magnetic powder
[0157] Particle size distribution
[0158] The particle size distribution of the soft magnetic powder of each sample No. was measured. It should be noted that the measurement was performed using a laser diffraction particle size distribution measuring device MICROTRAC, HRA9320-X100 manufactured by Nikkiso Co., Ltd. Then, the particle size D10, D50, D90 and (D90-D10) / D50 of the soft magnetic powder were calculated from the particle size distribution. The calculation results are shown in Table 1 or Table 2.
[0159] 7.2. Coercivity
[0160] The coercive force of the soft magnetic powder of each sample No. was measured using VSM system TM-VSM1230-MHHL manufactured by Tamagawa Seisakusho Co., Ltd. as a magnetization measuring device. The measurement results are shown in Table 1 or Table 2.
[0161] 8.Manufacturing of pressed powder cores and magnetic components
[0162] Using the soft magnetic powder of each sample No., a powder magnetic core and a magnetic element were produced in the following manner.
[0163] First, soft magnetic powder, epoxy resin (binding material) and methyl ethyl ketone (organic solvent) were mixed to obtain a mixture. The amount of epoxy resin added was 2 parts by mass based on 100 parts by mass of the soft magnetic powder.
[0164] Next, the obtained mixture was stirred and then dried by heating at 150° C. for 30 minutes to obtain a block-shaped dry product. Next, the dry product was passed through a sieve with a mesh size of 500 μm and pulverized to obtain a granulated powder.
[0165] Next, the obtained granulated powder was filled into a molding die to obtain a compact under the following molding conditions.
[0166] Forming method: stamping
[0167] Shape of the molded body: Ring
[0168] · Molding size: outer diameter inner diameter Thickness 3mm
[0169] Molding pressure: Molding pressure 294MPa
[0170] Next, the binder in the molded body is cured by heating, thereby obtaining a powder magnetic core (toroidal magnetic core).
[0171] Next, the obtained powder magnetic core was used to produce a Figure 1 Magnetic components shown.
[0172] ·Construction material of the conductor: Cu
[0173] Wire diameter: 0.6mm
[0174] Number of turns (when measuring magnetic permeability): 7 turns
[0175] Number of turns (for core loss measurement): 36 turns on the primary side, 36 turns on the secondary side
[0176] 9. Evaluation of magnetic components
[0177] 9.1. Magnetic permeability
[0178] The magnetic permeability of the magnetic element produced using the soft magnetic powder of each sample No. at a frequency of 100 kHz was measured using a 4294A precision impedance analyzer (Precision Impedance Analyzer) from Agilent. The obtained magnetic permeability was evaluated according to the following evaluation criteria.
[0179] A: Magnetic permeability is above 20
[0180] B: Magnetic permeability is greater than 17 and less than 20
[0181] C: Magnetic permeability is greater than 14 and less than 17
[0182] D: Magnetic permeability is less than 14
[0183] The evaluation results are shown in Table 1 or Table 2.
[0184] 9.2. Core loss
[0185] The core loss Pcv was measured for the magnetic element produced using the soft magnetic powder of each sample No. It should be noted that the measurement conditions were a measurement frequency of 1 MHz and a maximum magnetic flux density Bm of 50 mT. The obtained core loss was evaluated according to the following evaluation criteria.
[0186] A: Core loss is very low (less than 200kW / m in Table 1 3 , less than 400kW / m in Table 2 3 )
[0187] B: The core loss is slightly lower (200kW / m in Table 1) 3 Above and less than 250kW / m 3 , 400kW / m in Table 2 3 Above and less than 500kW / m 3 )
[0188] C: The core loss is slightly higher (250kW / m in Table 1). 3 Above and less than 300kW / m 3, 500kW / m in Table 2 3 Above and less than 600kW / m 3 )
[0189] D: The core loss is very high (300kW / m in Table 1). 3 Above, in Table 2 it is 600kW / m 3 above)
[0190] The evaluation results are shown in Table 1 or Table 2.
[0191] [Table 1]
[0192]
[0193] [Table 2]
[0194]
[0195] As can be seen from Tables 1 and 2, the soft magnetic powder of the example has lower coercivity than the soft magnetic powder of the comparative example. In addition, the magnetic element using the soft magnetic powder of the example also has good magnetic permeability and core loss.
[0196] It should be noted that the coercive force of the soft magnetic powders of the examples and comparative examples was 8.0 [Oe] or more without heat treatment. Therefore, it can be seen that the present invention can provide a soft magnetic powder that can achieve a sufficiently low coercive force through heat treatment and can achieve a high magnetic permeability.
Claims
1. A soft magnetic powder, characterized in that: Contains: Amorphous metal particles having a composition formula of Fe 100-a-b-c-d-e-f-g Cr a Si b B c C d Al e Ti f Co g The composition of the representation, Wherein, a, b, c, d, e, f and g are numbers representing atomic % and satisfy: 0<a≤3.0, 5.0≤b≤15.0, 7.0≤c≤15.0, 0.1≤d≤3.0, 0<e≤0.016, 0<f≤0.009, 0≤g≤0.025, e and f of the composition formula satisfy 0.20≤e / f≤2.50, In the composition formula, e and g satisfy 0.10≤e / g≤3.
00.
2. A powder magnetic core, characterized in that: Contains the soft magnetic powder according to claim 1.
3. A magnetic element, characterized in that: A powder magnetic core according to claim 2 is provided.
4. An electronic device, characterized in that: A magnetic element according to claim 3.
5. A mobile body, characterized in that: A magnetic element according to claim 3.
Citation Information
Patent Citations
Iron-based metallic glass alloy powder
JP2014169482A
Iron-base multiphase magnetic alloy material and preparation method thereof
CN102832001A
Soft Magnetic Powder, Powder Magnetic Core, Magnetic Element, And Electronic Device
CN108735416A